Scaling-up psychological interventions in resource-poor settings: training and supervising peer volunteers to deliver the 'Thinking Healthy Programme' for perinatal depression in rural Pakistan. (26th April 2019) - Atif, N.; Nisar, A.; Bibi, A.; Khan, S.; Zulfiqar, S.; Ahmad, I.; Sikander, S.; Rahman, A.
Abstract : Background: There is a scarcity of specialist trainers and supervisors for psychosocial interventions in low- and middle-income countries. A cascaded model of training and supervision was developed to sustain delivery of an evidence-based peer-delivered intervention for perinatal depression (the Thinking Healthy Programme) in rural Pakistan. The study aimed to evaluate the model. Methods: Mixed methods were employed as part of a randomised controlled trial of the intervention. Quantitative data consisted of the peers' competencies assessed during field training and over the implementation phase of the intervention, using a specially developed checklist. Qualitative data were collected from peers and their trainers through 11 focus groups during the second and third year of intervention rollout. Results: Following training, 43 peers out of 45 (95%) achieved at least a 'satisfactory' level of competency (scores of ⩾70% on the Quality and Competency Checklist). Of the cohort of 45 peers initially recruited 34 (75%) were retained over 3 years and showed sustained or improved competencies over time. Qualitatively, the key factors contributing to peers' competency were use of interactive training and supervision techniques, the trainer–peer relationship, and their cultural similarity. The partnership with community health workers and use of primary health care facilities for training and supervision gave credibility to the peers in the community. Conclusion: The study demonstrates that lay-workers such as peers can be trained and supervised to deliver a psychological intervention using a cascaded model, thus addressing the barrier of scarcity of specialist trainers and supervisors.